2008
DOI: 10.17796/jcpd.32.4.f53343t742150l73
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Oral Candidiasis in Chronic Renal Failure and Renal Transplant Pediatric Patients

Abstract: The objective of this study was to evaluate the prevalence and risk factors associated with candidiasis in chronic renal failure (CRF) and renal transplant (RT) patients. A cross-sectional study was made of 66 patients who were divided into 2 groups: group A (33 patients), RT patients, and group B (33 patients), who had been diagnosed with CRF. Data with respect to demographics, treatment type and duration, clinical laboratory results for blood leucocytes, oral hygiene, and diagnosis of oral candidiasis were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 23 publications
1
30
0
3
Order By: Relevance
“…that assessed samples of subgingival plaque and saliva from adult patients undergoing HD therapy. Likewise, Olivas‐Escárcega et al . did not find any significant difference in relation to oral cavity colonization by C. albicans among transplanted and CKD patients.…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…that assessed samples of subgingival plaque and saliva from adult patients undergoing HD therapy. Likewise, Olivas‐Escárcega et al . did not find any significant difference in relation to oral cavity colonization by C. albicans among transplanted and CKD patients.…”
Section: Discussionmentioning
confidence: 88%
“…The data in the literature show that local and systemic factors can alter the Candida load in patients’ oral cavities. Previous studies have shown that this occurrence can vary according to ethnicity and gender (males may be more commonly affected than females) and can increase with age. In a study performed by Yazdani et al ., the authors described higher colony counts in women than in men, but they found no association with age.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations